Legal Consequences of The Nominee Agreement Law in The Ownership of Land or Buildings by Foreign Nationals - Gaung Aydakarina Chusnul Khotimah (LEGAL BRIEF, 2022)
Along with the times and along with the current investment climate in Indonesia, the practice of Nominee Agreements is carried out secretly, not only in the case of Limited Liability Companies but also in cases of land or property.  The prices of land and property in Indonesia are getting higher and higher.  This increasingly attracts the upper middle class to buy and sell property or land for investment purposes.  This investment can bring its own advantages for investors.  The practice of the Nominee Agreement occurs when a foreigner who travels or who stops in Indonesia is then interested in owning the land or property, he will practice borrowing his name or nominee from relatives or family who are Indonesian citizens.  The Indonesian person borrowed his name to be written in a land certificate to trick the government so that it would not be discovered that the original owner was a foreigner.  property field.  Individual Indonesian Citizens whose names are used are not always from relatives but can also be from husbands or wives who are married or have mixed marriages between Indonesian Citizens and Foreign Citizens.  This can have an impact on the name of the asset ownership listed in a certificate of title to a land or property.  The nominee agreement has never been justified by Indonesian law, because it is contrary to the philosophy of the Basic Agrarian Law.